The Centrality of Communication and Media in Fostering Community Resilience: A Framework for Assessment and Intervention. (February 2015) - Houston, J. Brian; Spialek, Matthew L.; Cox, Joy; Greenwood, Molly M.; First, Jennifer
A community is resilient if it is able to "bounce forward" after an adverse event. Community resilience is generally considered a process that is indicated by community adaptation following a disaster or crisis. In this article, we employ media and communication perspectives (communication ecology, public relations, and strategic communication) to review the community resilience literature and propose a revised community resilience model. Our proposed model includes four components: communication systems and resources, community relationships, strategic communication processes, and community attributes. Each of these components includes several elements that are described. Implications for research and practice are discussed.